Analysis of Patentability on Research Results of Lecturers at Universitas Negeri Surabaya and Implementation of Patent Drafting: A Case Study - Tukiran, Tukiran; Wilujeng, Biyan Yesi (Proceeding Series of International Conference on Arts and Humanities, 2022)
The main purpose of this research is to find out the patenability of the research results of Unesa lecturers through PNBP funding for the fiscal year of 2022 and to find out the number of patents after the patent drafting activity. The research methods and stages included documentation analysis, implementation of patent drafting activities, and questionnaire analysis for before and after patent drafting activities. The results of the documentation analysis showed that there were 63 out of 806 lecturers’ research titles with potential patents (7.8%). Then, the patent drafting activity was carried out well by inviting 5 highly competent persons in the fields of IT, mechanics and machinery, electrical engineering, science, and arts and humanities. The results of the questionnaire analysis before the activity stated that from 46 respondents: 1) 87% of respondents stated that the output of their researches was believed to be patentable and the rest are not, 2) 67.4% of respondents had produced patents for their researches and the rest were not patents, and 3) 63% respondents have never compiled a patent and the rest have. Although, all of respondents (100%) knew that the patent is very useful. After the activity, there were 29 respondents who filled out the questionnaire. They stated that all presenters were declared good and very good in terms of all aspects of the assessment. Furthermore, all respondents gave an assessment between good and very good (> 90%) for the activities covering all aspects. This means that the activity was declared successful. Also, it is certain that the number of patents that have been successfully assisted have been registered with the DJKI system, although not all of them. The end of the drafting activity has resulted in 13 patents, of which 8 patents have been registered with the DJKI system.